Pentingnya Transportasi Umum untuk Kepentingan Publik - A. Caroline Sutandi (Centre for Public Policy and Management Studies, 2015)
Metropolitan cities with population of more than two million people and various activities i.e. economy, social, culture, education, and tourism, will automatically attract satellite cities. Impact of certain activities, poor land use, and limited infrastructure development physically leads to the increase of travel necessities which then causes traffic congestion almost during the whole day. One of the aspects needed to create a sustainable metropolitan city is good public transportation. The case study is carried out in Bandung. Based on existing conditions found in Bandung's public transportation, with paratransit as common public transportation and a limited number of mass rapid transit, therefore proposed alternative solutions could be as follow: the availability of city regulation, effort to reduce traffic congestion, orderly operation of paratransit, fixed route of medium and large bus operation, adherence of road users to traffic regulation, and good land use management, that involve all stakeholders.